Little Polar Bear and the husky pup - De Beer, Hans.; Lanning, Rosemary (New York : North-South Books, 1999)
Lars the Little Polar Bear rescues a stranded husky puppy and helps her find food and her mother.
13
Keywords: Bears -- Fiction; Dogs -- Fiction; Polar bear -- Fiction